Racial Difference as Violence: Colorblindness and Post-racialism in Anti-Affirmative Action Court Cases. - Acholonu, Ikenna. (2017)
Abstract: This thesis uses Critical Race Theory (CRT) and Frantz Fanon`s theory of violence to explore the questions: What discourses on race and affirmative action have the Supreme Court constructed and how do they connect to larger U.S. ideologies surrounding race? To answer these questions I conduct a Critical Race discourse analysis of three anti-affirmative action court cases: Grutter v. Bollinger (2003), Parents Involved in Community Schools v. Seattle School District No. 1 (2007), and Abigail Fisher v. University of Texas Austin (2013). I describe the Court`s use of a "race-neutral aspiration" discourse, a "cultural deficit" discourse, and a "White racial innocence" discourse to undermine affirmative action. I argue that these discourses are part of larger racial ideologies--colorblindness and post-racialism--where racial difference is violent toward people of color, as it decouples race from power. The conclusion of this thesis discusses this violence at selective universities, particularly through diversity.; Thesis (M.A.)--Tufts University, 2013.; Submitted to the Dept. of Education.; Advisor: Freeden Oeur.; Committee: Karen Gould, and Sabina Vaught.; Keywords: Higher education, Ethnic studies, and Law.